ANALYSIS OF SPEECH FUNCTION IN MILEY CYRUS’S SELECTED SONGS LYRICS: SYSTEMIC FUNCTIONAL LINGUISTIC - Nurul Laiyinah; Verayanti Verayanti; Desmalia Purba (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2022)
This thesis is entitled Analysis of Speech Function in Miley Cyrus’s Selected Songs Lyrics: Systemic Functional Linguistic. It discussed about speech function used in Cyrus’s selected songs lyrics. The objectives of the study were to find out; the types of speech function, the most dominant types, and the reasons of the most dominant types. It was conducted by using descriptive qualitative research. The data of this research were taken from 15 (fifteen) new and old songs of Miley Cyrus. This research used Halliday theory (1994) in analyzing how speech function and its types namely; statement, question, offer, and command work in the song lyrics. The data were analyzed by reading, listening, and taking notes. As the result taken, found 4 (four) types of speech function in the song lyrics, they are; Statement for 568 clauses (82%), Command for 74 clauses (10,69%), Question for 45 clauses (6,50%) and the least, Offer for 5 clauses (0,72%). The result of percentage indicates Statement (82%) and Command (10,69%) as the dominant types. The reasons of the dominant types are the composers dominantly using statement and command in intent of expressing the singer’s thoughts and feelings, giving personal/non-personal information and motivating the hearer to do better.